Measurement of the transverse polarization of Λ and Λ ¯ hyperons produced in proton-proton collisions at s =7TeV using the ATLAS detector - Onofre, A. (2015)
The transverse polarization of Λ and Λ¯ hyperons produced in proton--proton collisions at a center-of-mass energy of 7 TeV is measured. The analysis uses 760 μb−1 of minimum bias data collected by the ATLAS detector at the LHC in the year 2010. The measured transverse polarization averaged over Feynman xF from 5×10−5 to 0.01 and transverse momentum pT from 0.8 to 15 GeV is −0.010±0.005(stat)±0.004(syst) for Λ and 0.002±0.006(stat)±0.004(syst) for Λ¯. It is also measured as a function of xF and pT, but no significant dependence on these variables is observed. Prior to this measurement, the polarization was measured at fixed-target experiments with center-of-mass energies up to about 40 GeV. The ATLAS results are compatible with the extrapolation of a fit from previous measurements to the xF range covered by this mesurement.